2002
DOI: 10.1046/j.0028-646x.2001.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

A model coupling foliar monoterpene emissions to leaf photosynthetic characteristics in Mediterranean evergreen Quercus species

Abstract: Summary• A model was developed and parameterized to simulate monoterpene emission rates per unit leaf area (E) dependent on foliar photosynthetic potentials and activity of monoterpene synthases in the evergreen sclerophylls Quercus coccifera L. and Q. ilex L.• Assuming that total activity of monoterpene synthases controls the pathway flux, the product of leaf dry mass per unit area E was culculated as the fraction of total electron flow used for monoterpene synthesis (ε), the rate of photosynthetic electron t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 138 publications
8
128
2
2
Order By: Relevance
“…5 reveals a mean value of 2.4%. Niinemets et al (1999Niinemets et al ( , 2002b demonstrated that photosynthetic electron transport can be used to successfully simulate diel time-courses of isoprenoid emissions. The maximum rate of electron transport shows a strong positive correlation with the maximum rate of carboxylation and the inherent capacity of the enzyme responsible for CO 2 assimilation (Ribulose-1,5-bisphosphate carboxylase/oxygenase, RuBP) (Medlyn, Loustau & Delzon 2002) among plant species.…”
Section: Link Between Isoprene Emission Capacity and Gross Photosynthmentioning
confidence: 99%
See 1 more Smart Citation
“…5 reveals a mean value of 2.4%. Niinemets et al (1999Niinemets et al ( , 2002b demonstrated that photosynthetic electron transport can be used to successfully simulate diel time-courses of isoprenoid emissions. The maximum rate of electron transport shows a strong positive correlation with the maximum rate of carboxylation and the inherent capacity of the enzyme responsible for CO 2 assimilation (Ribulose-1,5-bisphosphate carboxylase/oxygenase, RuBP) (Medlyn, Loustau & Delzon 2002) among plant species.…”
Section: Link Between Isoprene Emission Capacity and Gross Photosynthmentioning
confidence: 99%
“…Due to the high K m value of isoprene synthase, poor substrate availability due to partitioning to competing pathways may prevent isoprene synthase to be active. Even though it is questionable whether isoprenoid synthesis is ever limited by photosynthesis, as isoprenoid synthesis requires only a few percent of total photosynthetic turnover of reduced carbon, ATP and NADPH (Niinemets et al 2002b), this physiological regulation of isoprene biosynthesis would be consistent with the Carbon-Nutrient Balance Hypothesis (CNB) and/or the Growth-Differentiation Balance Hypothesis (GDB) (Litvak, Constable & Monson 2002). CNB and GDB assume that the synthesis of carbon-rich secondary compounds is limited by the availability of photosynthates (i.e.…”
Section: Link Between Isoprene Emission Capacity and Gross Photosynthmentioning
confidence: 99%
“…The models implemented can be applied alternatively or in addition to each other (for more information see Grote, 2007;Grote et al, 2009a, b;Holst et al, 2010). In the current context the short-term isoprenoid emission models MEGAN , GUENTHER (Guenther et al, 1993), NIINEMETS (Niinemets et al, 2002a), and BIM2 (Grote et al, 2006) are coupled with models describing the canopy micro-climate within the canopy (ECM, Grote et al, 2009a) and the soil (DNDC, Li et al, 1992), photosynthesis (FARQUHAR, Farquhar and Von Caemmerer, 1982), phenology (SIM, Lehning et al, 2001;Grote, 2007), and soil hydrological conditions (QUERCUS, Rambal et al, 1993Rambal et al, , 2003) (see Fig. 1 and model descriptions below).…”
Section: Modelling Frameworkmentioning
confidence: 99%
“…NIINEMETS: This model (Niinemets et al, 2002a) for isoprene and monoterpene emissions takes a more processbased approach. It links the emission rates to synthase enzyme activity (S S ) to predict the capacity of isoprenoid synthesis as well as to foliar photosynthetic metabolism via the photosynthetic electron transport rate, J , to predict substrate (Niinemets et al, 1999;Niinemets et al, 2002a).…”
Section: Emission Modelsmentioning
confidence: 99%
“…The empirical algorithms have been recently criticized by Niinemets et al (2010a, b), based on the missing physico-chemical controls and lack of spatio-temporal resolution in the empirical approach. Monoterpene production is controlled by temperature and light conditions, but also the CO 2 concentration and compound volatility influence either the production or diffusion from tissues, thus some process-based models taking into account these dynamic factors have been developed for isoprene and monoterpenes (Niinemets et al, 2002;Possell et al, 2005;Arneth et al, 2007;Schurgers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%